2009
DOI: 10.1111/j.1750-3841.2008.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Discoloration Characteristics of 3 Major Muscles From Cattle During Cold Storage

Abstract: Discoloration characteristics of 3 major muscles (LD, Longissimus dorsi; PM, Psoas major; SM, Semimemebranosus) from Korean native cattle (Hanwoo) were monitored during 7 d of cold storage at 4• C. The muscles were obtained from 12 Hanwoo carcasses at 24 h postmortem. Meat color (CIE L*, a*, b*), myoglobin (Mb) concentration, chemical form, metmyoglobin (MetMb) reducing ability (MRA), mitochondria concentration, and thiobarbituric acid reactive substance (TBARS) were measured at 1, 3, 5, and 7 d of storage. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 22 publications
1
54
2
7
Order By: Relevance
“…Greater Mb concentrations are often associated with the accelerated discoloration in beef (Jeong et al, 2009;King et al, 2011). However, the results from the present study did not agree with this association observed in beef; while fallow deer IS and LTL demonstrated lower Mb content than BF, IS was more color stable than LTL and BF.…”
Section: Biochemical Attributes Influencing Surface Color Stabilitycontrasting
confidence: 57%
“…Greater Mb concentrations are often associated with the accelerated discoloration in beef (Jeong et al, 2009;King et al, 2011). However, the results from the present study did not agree with this association observed in beef; while fallow deer IS and LTL demonstrated lower Mb content than BF, IS was more color stable than LTL and BF.…”
Section: Biochemical Attributes Influencing Surface Color Stabilitycontrasting
confidence: 57%
“…www.meatandmusclebiology.com 1977a; O' Keeffe and Hood, 1982;Renerre and Labas, 1987;McKenna et al, 2005;Von Seggern et al, 2005;Jeong et al, 2009;Kim et al, 2009;Joseph et al, 2012;Canto et al, 2016). Intermuscular variations critically influence the color shelf-life of packaged fresh beef, with some muscles discoloring at a faster rate than the others (Hood, 1980).…”
Section: Muscle Sourcementioning
confidence: 99%
“…Since OC is dependent on residual mitochondrial activity, it is linked to muscle fiber type. Oxidative fibers contain more mitochondria and would thus have higher OCR than glycolytic fibers (Beecher et al, 1965;Beecher et al, 1969;Jeong et al, 2009). This, in part, explains the low color stability of muscles with higher proportions of oxidative fibers.…”
Section: Muscle Sourcementioning
confidence: 99%
“…Meat color is influenced by many factors, such as the concentration of heme pigments (especially myoglobin), the chemical state of myoglobin and the physical characteristics of the meat (Jeong et al, 2009). Although other heme proteins such as hemoglobin and cytochrome C may also play a role in meat color, myoglobin, the sarcoplasmic heme protein, is the principle protein responsible (Mancini and Hunt, 2005).…”
Section: Introductionmentioning
confidence: 99%